PELANGGARAN ETIKA PENDIDIKAN PADA SISTEM PEMBELAJARAN E-LEARNING - Ahmad Setiadi (Universitas Bina Sarana Informatika, 2015)
The development of information and communication technology is so rapid an impact on almost all aspects of life, including the education system. E-learning is emerging as an alternative form of education in the implementation of learning systems that allow the implementation is done anytime and anywhere. Nowadays, e-learning still has some shortcomings, particularly in terms of controlling student behavior that leads to educational ethics violations. Therefore, it is necessary to have a good understanding of the causes of violations of ethics in e-learning system, it is needed to know the types of ethical violations in the e-learning system and the important of preventive measures against ethical violations that may occur in e-learning system.Keywords: Educational Ethics, Learning System, E-Learning